Fenomena Sosial Ekonomi Penyintas Kelurahan Lere Pasca Gempa dan Tsunami - Hendra, Hendra; Laurang, Linda; Dewi, Citra (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2023)
This study develops understanding from the perspective of adaptation and strategies that are unique to humans as cultural creatures. However, this study develops deeper by revealing the cultural acceleration of humans using/activating their potential in overcoming the crisis conditions that surrounded them at that time. Therefore, this study site is placed in community life after a natural disaster in Lere Village, West Palu District, Palu City. This study uses a case study approach by highlighting the post-tsunami phenomenon which only took place 1 year after 28 September 2018. The results of the study show that the cultural acceleration that is developed relies heavily on social, cultural conditions and material availability. People are required/pressured to experience sudden and urgent conditions, they will continue to develop accelerated actions based on the conditions and phenomena they are living at that time, as a form of negotiation and compromise regarding their lives.